Phytochemistry, Pharmacological Properties and Medicinal Uses of Apium leptophyllum: A Review - Sheikh, Tariq Ahmad; Ganie, Shahid Yousuf; Reshi, Mohd Salim (Pharmacognosy Reviews)
Apium leptophyllum seeds are used as an important drug in Ayurveda from ancient times. The main constituents of the seed are fats, fibre, carbohydrates and essential oils, about 50% of which consists of Thymol. Chromatographic analysis of the seed showed various essential compounds viz. Pentacosanol, β-Sitosterol, 1-nonadecanol, 8-hydroxy cuminic acid, Corosolic acid and Stigmasterol. The seeds have shown strong antioxidant properties along with various other pharmacological properties like anti-microbial, anti-fungal, anti-diabetic, anti-inflammatory, anti-diarrheal, anti asthmatic and anti-cancer properties. This review aims to provide a comprehensive overview of scientific research literature on the chemical composition and pharmacological activities of Apium leptophyllum. We are the first to report vast and updated review of this plant, as much of the work has not been done on this plant. So this review may be helpful for the researchers to explore the pharmacological properties of this plant which may lead to new discoveries in drug development.
Keywords: Pharmacology; Phytochemistry; Antioxidant